Dictionary of the history of ideas : studies of selected pivotal ideas - Wiener, Philip Paul (Charles Scribner's, 1973)
v.1. Abstraction in the formation of concepts to design argument - v.2. Despostism to law, common - v.3. Law, concept of to protest movements - v.4. Psychological ideas in antiquity to Zeitgeist - v.5. Index.